INTELLECTUAL CAPITAL EFFICIENCY AND MARKET STRUCTURE OF ISLAMIC COMMERCIAL BANKS IN INDONESIA - Junio, Wilson; Kornitasari, Yenny (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2024)
This study investigates the impact of Intellectual Capital on the market structure of Islamic commercial banks in Indonesia. Employing a quantitative approach, the research utilizes the Random Effect Model for panel data regression analysis, drawing on secondary data extracted from the annual reports of eight Islamic commercial banks in Indonesia. The findings reveal that Islamic banks in Indonesia predominantly operate within a monopolistic market structure. Among the dimensions of Intellectual Capital, Human Capital Efficiency (HCE) emerges as the sole factor exerting a positive and significant influence on market structure, significantly enhancing the value creation process within Islamic banking. In contrast, Structural Capital Efficiency (SCE), Capital Employed Efficiency (CEE), and Relational Capital Efficiency (RCE) exhibit no discernible individual effects. These results underscore the necessity for regulators to delve deeper into market dynamics to foster a more competitive environment for Islamic banks. Furthermore, the findings advocate for regulatory support to facilitate the consolidation of Islamic banks, thereby enhancing Intellectual Capital efficiency. Such measures would enable Islamic banks to evolve into more efficient financial institutions, ultimately delivering greater societal benefits.